2012
DOI: 10.1039/c2cc30234a
|View full text |Cite
|
Sign up to set email alerts
|

Potent divalent inhibitors with rigid glucose click spacers for Pseudomonas aeruginosa lectin LecA

Abstract: The synthesis of a new rigid spacer based on carbohydrate-triazole repeating units and their incorporation into divalent systems is described. Inhibition studies showed that a well-matched system with a rigid spacer with flexible ends leads to the most potent inhibition of Pseudomonas aeruginosa lectin LecA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
78
1
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 77 publications
(85 citation statements)
references
References 34 publications
(5 reference statements)
4
78
1
2
Order By: Relevance
“…This tetrameric lectin binds galactosides and the shortest distance between two binding sites is around 26 Å [20,28]. We previously noted that the use of a rigid spacer with some flexibility in the aglycon chain connecting the galactose ligands, led to more potent inhibition [10]. Since the distance to cover is ca.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…This tetrameric lectin binds galactosides and the shortest distance between two binding sites is around 26 Å [20,28]. We previously noted that the use of a rigid spacer with some flexibility in the aglycon chain connecting the galactose ligands, led to more potent inhibition [10]. Since the distance to cover is ca.…”
Section: Resultsmentioning
confidence: 99%
“…The inhibitory potency of 22 for LecA was studied in an ELISA type assay by using a glycochip as the solid phase [10]. In this assay an IC 50 value of 0.9 μM was determined (Table 1).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…[61][62][63] Pieters et al reported bivalent galactosides which are thought to bind simultaneously to two of the four carbohydrate binding sites of LecA as concluded from the high potency (IC 50 = 220 nM). [64] LecB displays an unusually strong affinity for α-fucosides in the high nanomolar range, which could be explained by the crystal structure of the complex: [65] the presence of two calcium ions in the binding site and an additional lipophilic contact of the methyl group contribute to the strong binding. The blood group antigen Lewis a (26), bearing a terminal α-fucoside, is the best known monovalent ligand of LecB (K d = 220 nM).…”
Section: Ta Rgeting Quorum Sensingmentioning
confidence: 99%